Somatosensory cross-modal activation and changes in cortical somatosensory evoked potential responses in single-sided deafness: an EEG study - Sofack, Ghislain; Raouafi, Kotaiba; Heinrich, Sven P.; Aschendorff, Antje; Wesarg, Thomas; Arndt, Susan; Sandmann, Pascale; Speck, Iva (Frontiers in Neuroscience, 2025)
BackgroundThe neural mechanisms underlying somatosensory processing in individuals with acquired single-sided deafness (SSD) and potential central neuronal cross-modal reorganization remain largely unexplored. This study investigates the impact of SSD on somatosensory perception and attentional processing.MethodsElectrophysiological responses using EEG, and behavioral measures (discrimination thresholds, hit rates and reaction times) were assessed in adults with acquired SSD and normal-hearing (NH) controls for vibrotactile stimulation at two distinct frequencies. Differences in cortical somatosensory evoked potentials between adults with acquired SSD and normal-hearing (NH) controls, focusing on peak amplitudes and peak times of key event-related potential components (P50, N70, P100, N140, and P3b) and their cortical generators were assessed.ResultsWhile both groups exhibited comparable behavioral performance, significant differences emerged in electrophysiological responses. Individuals with SSD showed increased P3b amplitude (albeit non-significant) and significantly delayed P3b peak times, indicating that individuals with acquired SSD exhibit alterations in attentional mechanisms associated with somatosensory perception. In addition, source localization analysis of the P50 component using standardized low-resolution brain electromagnetic tomography (sLORETA) revealed group differences in cortical activation patterns, with SSD individual showing additional recruitment of auditory-related areas, including the superior temporal gyrus, the middle temporal gyrus and the insula. This further supports the notion of compensatory neuroplasticity in auditory pathways following severe to profound unilateral hearing loss.ConclusionOur results indicate that SSD is associated with neural reorganization in somatosensory and auditory pathways. The observed modifications in both early and late somatosensory responses, coupled with alterations in source activity, suggest that individuals with SSD engage alternative neural mechanisms when processing vibrotactile stimuli, differing from the typical patterns observed in NH individuals. Understanding these changes prior to cochlear implantation will facilitate the development of personalized auditory rehabilitation strategies following cochlear implantation.